Antiphospholipid Antibody Syndrome Presenting with Hemichorea - Yezenash Ayalew; Fazlihakim Khattak (Case Reports in Rheumatology)
A 25-year-old Bangladeshi lady presented to neurology with a three-month history of involuntary movements of her right arm, associated with loss of power. There was progression to the right leg, and she subsequently developed episodes of slurred speech and blurred vision. At the time of presentation, she was 12 weeks pregnant and the symptoms were reported to have started at conception. Past medical history was unremarkable apart from one first trimester miscarriage and there was no significant family history suggestive of a hereditary neurological condition. MRI of the head revealed no abnormalities but serology showed positive antinuclear antibodies (ANAs) at a titre of 1/400. Further investigations revealed strongly positive anticardiolipin antibodies (>120) and positive lupus anticoagulant antibodies. The patient had a second miscarriage at 19 weeks gestation strengthening the possibility that the chorea was related to antiphospholipid antibody syndrome and she was started on a reducing dose of Prednisolone 40 mg daily and aspirin 300 mg daily. Six months later, she had complete resolution of neurological symptoms. There are several reports of chorea as a feature of antiphospholipid syndrome, but no clear consensus on underlying pathophysiology.